2011
DOI: 10.3390/ijms12021293
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Annealing Temperature on the Optical Spectra of CdS Thin Films Deposited at Low Solution Concentrations by Chemical Bath Deposition (CBD) Technique

Abstract: Two different concentrations of CdCl2 and (NH2)2CS were used to prepare CdS thin films, to be deposited on glass substrate by chemical bath deposition (CBD) technique. CdCl2 (0.000312 M and 0.000625 M) was employed as a source of Cd2+ while (NH2)2CS (0.00125 M and 0.000625 M) for S2− at a constant bath temperature of 70 °C. Adhesion of the deposited films was found to be very good for all the solution concentrations of both reagents. The films were air-annealed at a temperature between 200 °C to 360 °C for one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 22 publications
(21 reference statements)
0
11
0
1
Order By: Relevance
“…The values of the absorption coefficient have been found to be in the range of 10 4 cm À1 in the Urbach region, which are in conformity with the results reported in a number of earlier works. 4,[18][19][20][21] The measured absorption coefficients are used to determine the band gap energy of the material by applying the relation a 2 ¼ A 2 (h À E g ), which corresponds to band-toband transition region near the absorption edge. As already discussed in Sec.…”
Section: Materials Deposition and Measurementsmentioning
confidence: 99%
“…The values of the absorption coefficient have been found to be in the range of 10 4 cm À1 in the Urbach region, which are in conformity with the results reported in a number of earlier works. 4,[18][19][20][21] The measured absorption coefficients are used to determine the band gap energy of the material by applying the relation a 2 ¼ A 2 (h À E g ), which corresponds to band-toband transition region near the absorption edge. As already discussed in Sec.…”
Section: Materials Deposition and Measurementsmentioning
confidence: 99%
“…It has been used as a window layer in high efficiency thin film solar cells base on cadmium telluride (CdTe), copper indium diselenide / sulphide (CIS) and copper indium gallium diselenide / sulphide (CIGS) [4]. It has been used in the deposition of CdS semiconductor thin films since the 1960s [5,6] and many techniques including electrodeposition [7,8], spray pyrolysis [9], successive ionic layer adsorption and reaction (SILAR) [10], vacuum evaporation [11], and Chemical Bath Deposition (CDB) [12][13][14]. CBD is known to be a simple method, with low temperature and inexpensive large area deposition technique, it use an aqueous solution and then we can control the chemical parameters of solution like (temperature, molar concentration, PH, time of deposition, stirring rate., etc.)…”
Section: Introductionmentioning
confidence: 99%
“…35 For instance, it has been reported that the decrease in lm resistivity is due to CdS oxidation (CdO), sulfur evaporation resulting in sulfur vacancies, removal of impurities, or morphological changes due to the grain growth with the concomitant reduction of grain boundaries. 35,[53][54][55] In order to understand the origin of the resistivity reduction aer annealing at 300 C for 60 min in air, the structural, physicochemical, and morphological properties of the lms reacted at 250 C with and without this additional annealing were studied. The results regarding thermal annealing in N 2 can be found in the ESI.…”
Section: Synthesis and Characterization Of Cadmium Sulde Thin Lmsmentioning
confidence: 99%